Influence of the Size Distribution of the SiC Powder Source on the Shape of the Crystal Growth Interface during PVT Growth of 4H-SiC Boules - Schultheiß, Jana; Ihle, Jonas; Nanot, S. Usseglio; Bonanomi, S.; Munoz, D. Callejo; Hammer, R.; Wellmann, Peter (Trans Tech Publications Ltd, 2024)
We compared the evolution of three different SiC sources during standard PVT growth runs. The evolution of the growing crystal and the morphological changes in the SiC source were visualized using in-situ X-ray visualization. Computer simulation was used to calculate the temperature field distributions. It is found that the densification and shrinkage of the SiC source material during the growth process can affect the growth conditions in such a way that the convexity of the growth interface is increased in an unfavorable manner. While unfavorable growth conditions can be related to thermal properties due to less favorable SiC powder evolution, predicting such behavior is a rather complex task that still relies on the support of experimental methods.
CRIS-Team Scopus Importer:2025-02-04
Keywords: mass transport; SiC PVT growth; SiC source material; temperature field